Laporan Hasil Praktik Profesi Asuhan Keperawatan Komunitas Di Kelurahan Periuk Jaya Rt 03/Rw 04 Kecamatan Periuk Kota Tangerang 2023 - Alfika Safitri; Nur Ayu Fazri; Aulia Shafa Shalsabila; Mesi Maesaroh; Pujianti Listiani; Mardiana Pratiwi; Veronnicka Shintya Dewi; Nurul Fadhilah; Astuti Astuti; Devi Sri Rahayu; Siti Sopiah; Dede Nurjanah; Febiola Dwi Puspitasari (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Community nursing or community health nursing is the practice of maintaining and improving public health using knowledge from nursing, social sciences and public health sciences. Another definition of community nursing is a form of professional service based on nursing knowledge and tips aimed primarily at high-risk groups to improve community health status by emphasizing efforts to improve health, disease prevention and not neglecting curative and rehabilitative (Kholifah & Widagdo, 2016). In RW 04 Kelurahan Periuk Jaya, which is a village with densely populated residential houses with houses attached to one another, the average building in Pabuaran village has new buildings but is not well maintained and settlements are dominated by old buildings. own property, in terms of the environment the area of ​​the house has a yard, there are several cattle pens around the settlement. The characteristics of the area and health problems that arise in RW 04 Periuk Jaya Village are information about prevention and diet for Hypertension, Gout Arthritis and ISPA. To carry out this task requires a person nurses who are competent in providing community nursing care, to get optimal results requires experience in addition to knowledge. One way to gain experience is through community nursing practice in Periuk Jaya Village RW 04 Periuk District, Tangerang City